b - d uthor.9 (b, 2004)
Articles on the 1971 liberation movement of Bangladesh; chiefly on the non-cooperation movement called by Bangabandhu Sheikh Mujibur Rahman.
Includes bibliographical references (page 80).
In Bengali.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Bangladesh -- History -- Revolution, 1971.